A lever-like transduction pathway for long-distance chemical- and mechano-gating of the mechanosensitive Piezo1 channel - Yanfeng Wang (Nature Portfolio, 2018)
Piezo1 is a large trimeric ion channel activated by mechanical stimulus. Here the authors identify chemical activators of Piezo1 that utilize a lever-like mechanotransduction pathway for long-range allosteric gating.